History of Chicha Grapes: A Typical Product in Chile [Historia de la Chicha de Uva: Un Producto Típico en Chile] - Lacoste, P (Universidad de Tarapaca, 2015)
The article examines the history of chicha, a typical product of Chile, which dates back to the Spanish colony. The beer is obtained from the partial fermentation of the grape juice. It was important for the Chilean agribusiness eighteenth century and reached its apogee in the nineteenth. Later, chicha was replaced with French wine grapes. But it remained rooted drink the rural population and the Chilean national holiday. The article examines the characteristics that had this product, its rise and fall, along with their current survival and official recognition. © 2015, Universidad de Tarapaca. All rights reserved.